Analisis Resources Nationalism pada Kebijakan Sektor Pertambangan Batubara terhadap Ketahanan Energi Indonesia - Sutrisno, Alya Triska; Hanita, Margaretha; Yoesgiantoro, Donny (UI Scholars Hub, 2021)
The Global Commodity Boom happened during 2003-2013 triggered increased price and demand for mineral and coal commodities around the world. The mineral and coal producing countries implement Resources Nationalism (RN). Indonesia as second of the largest coal exporting countries also indicates using RN in mineral coal policy. The aim of this study is to analyse RN in Indonesia coal’s sector based on Law Number 3 of 2020 and its implication toward Indonesia’s energy resilience. This qualitative research is aimed to describe the RN in Indonesia’s coal sector and risk analysis on coal sector to understand Indonesia energy resilience. Based on the result of this study, RN on Law Number 3 of 2020 was implemented by considering the ownership structure, intervention on operational industry and policy aimed to increase rent. Risk analysis related to availability, affordability, accessibility and acceptability. The result shows the positive impact arise include the guarantee of national energy availability, price stability and increasing industry capability related to coal. The negative impact is the environmental damage has potential to become burden on government in long term. Key Words: Coal, Energy Resilience, Resources Nationalism